Wheat–Fusarium graminearum Interactions Under Sitobion avenae Influence: From Nutrients and Hormone Signals - Luo, Kun; Ouellet, Thérèse; Zhao, Huiyan; Wang, Xiukang; Kang, Zhensheng (Frontiers in Nutrition, 2021)
The English grain aphid Sitobion avenae and phytopathogen Fusarium graminearum are wheat spike colonizers. “Synergistic” effects of the coexistence of S. avenae and F. graminearum on the wheat spikes have been shown in agroecosystems. To develop genetic resistance in diverse wheat cultivars, an important question is how to discover wheat–F. graminearum interactions under S. avenae influence. In recent decades, extensive studies have typically focused on the unraveling of more details on the relationship between wheat-aphids and wheat-pathogens that has greatly contributed to the understanding of these tripartite interactions at the ecological level. Based on the scientific production available, the working hypotheses were synthesized from the aspects of environmental nutrients, auxin production, hormone signals, and their potential roles related to the tripartite interaction S. avenae–wheat–F. graminearum. In addition, this review highlights the relevance of preexposure to the herbivore S. avenae to trigger the accumulation of mycotoxins, which stimulates the infection process of F. graminearum and epidemic of Fusarium head blight (FHB) in the agroecosystems.